Life pressures and their relationship to the meaning of life and satisfaction with it of university students (Journal of the College of Basic Education, 2022)
The current research aims to identify (life pressures) among university students and its relationship to (meaninglife) and (satisfaction with life); And the correlation between them + and the extent of the contribution of (the meaning of life)And (satisfaction with life) in the total change of (life pressures).The research sample consisted of (445) male and female students from Baghdad and Al-Mustansiriya universities. And doneApplication of measures (life stress, the meaning of life, and satisfaction with life) using a coefficientPearson correlation, remote test 1854-1 and stepwise multiple regression analysis showed resultssearch :1. There is a negative correlation between (life pressures) and both (the meaning of life) and (satisfaction).about life ) ; And a positive correlation between (the meaning of life) and (satisfaction with life)... (meaning of life) and (satisfaction with life) contribute (24.1%) to the total varianceFor (the pressures of life).